Desain Batasan Ruang Eksplorasi dalam Video Game terkait Imersifitas: Studi Kasus pada game Assasin’s Creed Series, GTA V & Uncharted 4 - Albar, Deni (Universitas Komputer Indonesia, 2025)
This study aims to explore the role of spatial boundaries in video games in shaping narrative and gameplay experience, particularly within the Role Playing Games (RPG) genre. Spatial boundaries not only function as elements of level design but also influence story structure, player interaction, and character development. Using a qualitative content analysis approach, the research highlights how spatial limitations shape immersive virtual environments and affect players’ motivations and narrative decisions. The findings reveal that spatial boundaries play a crucial role in creating alternative digital realities that can influence players’ perceptions of the real world. This study contributes to a deeper understanding of game design and opens up discussions on the sociocultural impact of video games, especially in shaping players’ views and interactions with digital realities. The insights gained are expected to drive innovation in the gaming industry and offer broader benefits in the development of digital culture, both as a form of entertainment and as an educational tool with constructive potential.